Nexam Chemical purchases Plasticolor Sweden to secure masterbatch production capacity. Issue 2 (February 2018) - Unknown
Abstract : Swedish plastics technology firm Nexam Chemical Holding AB has acquired compatriot Plasticolor Sweden AB, a privately owned masterbatch manufacturer. Headquartered in Lomma, near Malmö, Plasticolor Sweden has production facilities in four countries and generates annual turnover of about SEK86 million. The transaction was completed in December 2017.